2018
DOI: 10.1098/rsfs.2017.0039
|View full text |Cite
|
Sign up to set email alerts
|

On the utilization of novel spectral laser scanning for three-dimensional classification of vegetation elements

Abstract: The Dual-Wavelength Echidna Lidar (DWEL), a full waveform terrestrial laser scanner (TLS), has been used to scan a variety of forested and agricultural environments. From these scanning campaigns, we summarize the benefits and challenges given by DWEL's novel coaxial dual-wavelength scanning technology, particularly for the three-dimensional (3D) classification of vegetation elements. Simultaneous scanning at both 1064 nm and 1548 nm by DWEL instruments provides a new spectral dimension to TLS data that joins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 23 publications
(41 reference statements)
0
14
0
Order By: Relevance
“…() and Danson et al. (), proposed new equipment configurations, with two lasers of different wavelengths (Douglas et al., ), that would greatly improve the ability to separate wood and leaf points (Danson, Sasse, & Schofield, ; Hancock, Gaulton, & Danson, ; Li, Schaefer, Strahler, Schaaf, & Jupp, ; Li, Strahler, et al., ). Different materials present different reflectance, and exploiting the contrast between wavebands would assist the identification of such materials.…”
Section: Introductionmentioning
confidence: 99%
“…() and Danson et al. (), proposed new equipment configurations, with two lasers of different wavelengths (Douglas et al., ), that would greatly improve the ability to separate wood and leaf points (Danson, Sasse, & Schofield, ; Hancock, Gaulton, & Danson, ; Li, Schaefer, Strahler, Schaaf, & Jupp, ; Li, Strahler, et al., ). Different materials present different reflectance, and exploiting the contrast between wavebands would assist the identification of such materials.…”
Section: Introductionmentioning
confidence: 99%
“…In our formulation, one of the critical aspects is to be able to estimate a fraction of leaf hits F, as well as the leaf volume fraction α (Equation 13). The development of algorithms and methods for leaf and wood separation is a subject of active research [24][25][26][27][28][29], which is a prerequisite of most methods aiming at retrieving wood volume [22]. One could notice that determining the leaf fraction F is less challenging than the classification of each individual hit as "leaf" and "wood", in the sense that leaf fraction can be correctly estimated from a classification method with significant omission and commission errors inside the voxel.…”
Section: Discussionmentioning
confidence: 99%
“…The value of F can be determined from one of the algorithms and methods developed to discriminate leaf and wood returns [18,[24][25][26][27][28][29].…”
Section: Generalized Maximum-likelihood Estimation For Lad From Multimentioning
confidence: 99%
“…As a result, they can be applied to data acquired using different instruments and experimental protocols. Different approaches have been explored and tested using geometrical feature extraction and machine learning [33][34][35][36][37]. Tao et al [38] have shown that circle and line fitting on 2D projections of the 3D point cloud allowed a better wood/leaf separation than approaches based on intensity returns.…”
Section: Introductionmentioning
confidence: 99%